Street-gang and tribal-warrior autobiographies - Brumble, H. David (Book Network Int'l Limited trading as NBN International (NBNi) : Anthem Press, 2018)
'Street-Gang and Tribal-Warrior Autobiographies' describes the similarities between the autobiographies of warrior tribes and of street gangs. Gangbangers were so alienated from the larger society that they reinvented something very similar to tribal-warrior cultures right in the heart of American cities.